Identification of Fungi on the Scalp of Male Santri Wearing Peci at the AI Islah Islamic Boarding School, Kebagusan, Ampelgading, Pemalang - Pratama, Helmi Aji; Suparyati, Tuti (INDOGENIUS, 2025)
Background & Objective: Fungal infections of the scalp, particularly tinea capitis, are a common health problem in environments with poor hygiene, such as Islamic boarding schools (pondok pesantren). This study aims to identify the types of fungi infecting the scalps of male santri who regularly wear the peci (a traditional cap) at the Al-Ikhlas Islamic Boarding School in Kebagusan, Ampelgading, Pemalang. Method: The study used a descriptive method with a laboratory approach, involving culture on Sabouraud Dextrose Agar (SDA) medium and microscopic examination for fungal identification. Result: Out of 20 scalp scraping samples analyzed, 75% showed positive results for fungal infection. The most dominant fungus found was Aspergillus sp., while Candida sp. was found in only one sample (5%). No infections by Trichophyton or Microsporum were detected. Questionnaire results supported the laboratory findings, indicating that only 10.8% of santri regularly shampooed their hair, 13.5% washed their peci periodically, and 35.1% reported symptoms of scalp itching. Conclusion: This study demonstrates that the habit of wearing the peci without proper hygiene maintenance can be a significant risk factor for scalp fungal infections. Therefore, preventive efforts through personal hygiene education and routine examinations are needed to reduce the incidence of fungal infections in the pesantren environment.